Analysis Of The Influence Of Personality And Organizational Climate On Leadership In The Department Of Industry, Trade, Energy And Mineral Resources Of North Sumatera Province - Amelia Putri; Eli Delvi Yanti; Abdi Setiawan (Journal of Management, Economic, and Accounting, 2026)
This study aims to influence personality and organizational climate on leadership in the Department of Industry, Trade, Energy and Mineral Resources of North Sumatra Province. The research method used is quantitative, the data analysis technique is multiple linear regression with data processing using the SPSS version 25 program. The sample in this study was 68 employees. Primary data collection used a questionnaire. The results of the study indicate that personality has a positive and significant partial effect on leadership in the Department of Industry, Trade, Energy and Mineral Resources of North Sumatra Province seen from the results of t count (2.948> 1.997138) t table with sig. 0.004 <0.05 so that the results of the study accept H1. Organizational Climate has a positive and significant partial effect on leadership in the Department of Industry, Trade, Energy and Mineral Resources of North Sumatra Province seen from the results of t count (3.203> 1.997138) t table with sig. 0.002 <0.05 so that the results accept H2. Personality and Organizational Climate have a significant simultaneous influence on leadership in the Department of Industry, Trade, Energy and Mineral Resources of North Sumatra Province as seen from the results of F count 12.014 > F table 3.14 and sig. 0.000 < 0.05, so it can be concluded that H3 is accepted.